Pengaruh Model Think Pair Share Terhadap Minat Siswa Pada Mata Pelajaran IPS - Hari Kurniawan; Syaiful M; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2017)
The research was conducted in SMPN 16 Bandar Lampung with aim to The purpose of this study is to determine the Effect of Think Pair Share on the student interest with samples were twenty seven student ass eksperimental class and twenty seven student ass controll class use random technique from VII class population. Think Pair Share method. used is experimental class,and controll class used konvensional method with Posttest-Only Control Group Design design The data that has been collected is then processed manually using the Theta formula. And chis quare formula.The result shows that there is an effect with a theta correlation was 0,46 which fall into the category of significant or moderate and significance of the chi square value obtained at 10,14 .Penelitian ini dilaksanakan di SMPN 16 Bandar Lampung dengan Tujuan untuk mengetahui pengaruh model Think Pair Share terhadap minat siswa dengan sampel 27 siswa sebagai kelas eksperimen dan 27 siswa kelas kontrol yang secara acak terpilih dari semua kelas VII sebagai populasi. Model Think Pair Share diterapkan di kelas eksperimen, untuk kelas kontrol memakai model konvensional dengan desain Posttest-Only Control Group Design.Data diolah dengan rumus Theta dan Kai Kuadrat.Hasil menunjukan ada pengaruh dengan nilai korelasi Theta 0,46 yang termasuk cukup dan nilai signifikan Kai Kuadrat adalah 10,14Kata kunci: minat siswa,pelajaran IPS, think pair share